FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI PADA BIDANG SUMBER DAYA AIR DINAS PEKERJAAN UMUM DAN PENATAAN RUANG PROVINSI BENGKULU - Nia Indriasari; Oni Yulianti; Herawati Herawati (UNIVED Press, 2018)
Study aims to determine the dominant factors affecting the employees’ performance in the division of water resources at Dinas Pekerjaan Umum dan Penataan Ruang of Bengkulu Province. The most dominant factor / the highest affects the employees’ performance in the division of water resources at Dinas Pekerjaan Umum dan Penataan Ruang of Bengkulu Province is the quality factor of employment the division of water resources at Dinas Pekerjaan Umum dan Penataan Ruang of Bengkulu Province with the total value of the respondent's perception 884 with agreed criteria.The average of the respondents' answers to the overall factor is 862.86 in the agreed criteria, meaning that the average respondent agrees that the overall factor proposed can affect the employees performance in the division of water resources at Dinas Pekerjaan Umum dan Penataan Ruang of Bengkulu Province. The lowest factor affects the employees’ performance in the division of water resources at Dinas Pekerjaan Umum dan Penataan Ruang of Bengkulu Province is an innovation factor of the employees in the division of water resources at Dinas Pekerjaan Umum dan Penataan Ruang of Bengkulu Province with the number of values from the perception of respondents 829 with the criteria agreed.Key Words: Quality of work, quantity of work, job knowledge, teamwork, creativity, innovation, initiative